Penerapan Asas Keseimbangan dalam Perjanjian Pengadaan Barang/Jasa Pemerintah - Anastasia Regita Rintan Sahara; Imelda Martinelli (Jurnal Hukum Lex Generalis, 2025)
This article discusses the application of the principle of balance in public procurement agreements, which is a basic principle in ensuring equal rights and obligations between the parties involved. The principle of balance is particularly important in the context of public procurement, given the potential imbalances that can arise due to differences in bargaining power and interests between the government and the goods/services provider. This research explains how this principle should be implemented in every stage of the agreement, from negotiation, formation, to contract execution. In addition, this article also highlights the importance of written agreements in providing legal certainty and reducing potential disputes. This research uses a qualitative approach and library research method. The application of this principle not only strengthens trust between the parties involved, but also encourages more efficient and responsible procurement practices. As well as designing more balanced and equitable agreements.